Episyrphus balteatus symbiont variation across developmental stages, living states, two sexes, and potential horizontal transmission from prey or environment - Chang, Xiao; Xue, Shuang; Li, Ruimin; Zhang, Yuanchen (Frontiers in Microbiology, 2024)
Episyrphus balteatus is one representative Syrphidae insect which can provide extensive pollination and pest control services. To date, the symbiont composition and potential acquisition approach in Syrphidae remain unclear. Herein, we investigated microbiota dynamics across developmental stages, different living states, and two sexes in E. balteatus via full-length 16S rRNA genes sequencing, followed by an attempt to explore the possibility of symbionts transmission from prey Megoura crassicauda to the hoverfly. Overall, Proteobacteria and Firmicutes were the dominant bacteria phyla with fluctuating relative abundances across the life stage. Cosenzaea myxofaciens is dominant in adulthood, while Enterococcus silesiacus and Morganella morganii dominate in larvae and pupae of E. balteatus, respectively. Unexpectedly, Serratia symbiotica, one facultative endosymbiontcommonly harbored in aphids, was one of the predominant bacteria in larvae of E. balteatus, just behind Enterococcus silesiacus. Besides, S. symbiotica was also surprisingly most dominated in M. crassicauda aphids (92.1% relative abundance) significantly higher than Buchnera aphidicola (4.7% relative abundance), the primary obligate symbiont of most aphid species. Approximately 25% mortality was observed among newly emerged adults, of which microbiota was also disordered, similar to normally dying individuals. Sexually biased symbionts and 41 bacteria species with pairwise cooccurrence in E. balteatus, and 23 biomarker species for each group were identified eventually. Functional prediction showed symbionts of hoverflies and aphids both mainly focusing on metabolic pathways. Briefly, we comprehensively explored the microbiome in one Syrphidae hoverfly by using laboratory-reared E. balteatus on M. morganii as the model, revealed its dominated symbiont species, identified sexually biased symbionts, found an aphid facultative endosymbiont inhabited in hoverfly. We also found the dominant symbiont in M. crassicauda is S. symbiotica other than Buchnera aphidicola. Taken together, this study provides new valuable resources about symbionts in hoverfly and prey aphid jointly, which will benefit further exploring the potential roles of microbiota in E. balteatus.